Combination Therapy as a Strategy to Control Infections Caused by Multi-resistant Bacteria: Current Review - Hernandez-Rodriguez, Patricia; Baquero, Ludy P. (Current Drug Targets, 2022)
Antimicrobial Resistance (AMR) is one of the main challenges of today's medicine because it has become a global problem that affects the treatment of multiple infections and impacts public health. This resistance is caused as the bacteria generate selective pressure-promoting mechanisms to evade the action of conventional drugs, which are also associated with adverse effects. Infections caused by these multi-resistant bacteria potentially reduce the possibility of effective therapy; this situation increases morbidity and mortality and treatment costs. Therefore, to establish combined therapy as a strategy for the control of infections caused by multi-resistant bacteria, a bibliographic search was carried out between 2015 and 2020 in databases such as PubMed, Scopus and Science Direct. The exhaustive review of the articles allowed a critical analysis of the information. Mechanisms were identified for obtaining drugs with antimicrobial potential, their biological activity and the possible effect of their combination against multidrug-resistant bacteria as an alternative for infectious disease control and as a response to reduce the use of antibiotics. Combined therapy is presented as an innovative therapeutic alternative, which uses non-antibiotic substances that can be obtained by three routes: the repositioning of drugs, synthetic substances and natural products. In this way, important elements are provided to guide researches that seek to reduce antimicrobial resistance.
Keywords: drug combination